Electrification and performance analysis of hybrid PV solar/wind energy system for remote and hilly area of Uttarakhand (India). (2023) - Bahuguna, Neeraj Kumar; Bisht, Tanuj Kumar; Bhawana,; Sharma, Promila; Sharma, Neetu; Joshi, Harish Chandra; Meshrama, Sanjogta
Abstract: The need of electricity increases day by day, due to increase in population. With LPG cylinder rates touching stratospheric heights even though new LPG connections have been provided in the remote villages of Uttrakhand, people have no money to purchase the cylinders. Therefore it becomes a necessity to provide uninterrupted power to each family in each locality including remote and tribal's of Uttarakhand so that they can cook their food on induction tops instead of shifting back to smoky ways of producing fire. This Paper is for analysis of power supply using Solar and Wind hybrid energy system in belts that lie in north-east of Uttarakhand. This area includes some part of Dehradun, Tehri, Pithoragarh, Champawat, Bageshwar, Almora, some part of Nainital and Rudraprayag. There are some hilly/tribal areas where population is less than 30 persons per square kilometers. People in such areas live in scattered homes. The entire area having mountainous topography results in very costly supply of electricity to each and every home. Further continuous supply of electricity to these remote areas of Uttarakhand is also a big challenge. Hybrid Solar PV and Wind Energy is very useful for these areas. For rural area of Uttarakhand it plays a major role to fulfill the requirement of energy. Electrification of households in rural areas and isolated regions results in balanced economic development. India grows with a high population growth rate of 0.95 % in current year but still parts of rural India and isolated regions do not have the accessibility to electric power. This study focuses on the feasibility study of a hybrid PV-Wind-Energy power system for rural electrification in Uttarakhand.